The global financial crisis: Decoupling of East Asia - myth or reality? - Yung Chul Park (Asian Development Bank Institute (ADBI), 2011)
The decoupling of East Asia from its economic interactions - both in trade and finance - with the rest of the world refers to the phenomenon of a weakening of the impact of demand and supply shocks emanating from the advanced countries on the region's economic performance since the early 1990s. Available empirical evidence, including the faster recovery of East Asia from the 2008 global economic crisis, does not appear to lend credence to the decoupling thesis. However, with increases in income throughout the region and the three free trade agreements (FTAs) of the People's Republic of China (PRC), Japan, and Korea with the Association of Southeast Asian Nations (ASEAN) (which have entered into force), East Asia will witness a continuing expansion in intra-regional trade, much of which will consist of horizontal intra-industry trade. At the same time, if East Asia succeeds in instituting an efficient capital control regime and in strengthening the Chiang Mai Initiative Multilateralization (CMIM), it will be able to cope better with the volatility of capital flows to the region. Together these developments will then help speed up economic integration among ASEAN+3 member states to build a region that is more self-contained than it has been.
Keywords: E32; F15; R11; 330; Finanzmarktkrise; Makroökonomischer Einfluss; Internationale Wirtschaftsbeziehungen; Wirtschaftliche Anpassung; Handelsregionalismus; Kapitalverkehrspolitik; Ostasien